PTH-042 Spiral snare resection and hybrid endoscopic mucosal ablation: a comparison of outcomes after piecemeal resection/ablation. (22nd June 2015) - Tsiamoulos, ZP; Rameshshanker, R; Suzuki, N; Bourikas, L; Saunders, BP
Abstract : Introduction: Incomplete endoscopic removal of colorectal polyps causes severe submucosal fibrosis, making subsequent endoscopic resection challenging. Two approaches to removal of recurrent polyp over a scarred submucosa or to polyps with inherent submucosal fibrosis such as NG-LST's are either to use a stiff braided snare which helps capture tissue or to firstly snare as much tissue as possible using a conventional snare and then destroy tissue over the centre of the scar with high power APC preceded by submucosal injection (Endoscopic Mucosal Ablation, EMA). Method: A prospective database (Jan 2010–Aug 2012) was used to identify large (>2 cm) colorectal polyps removed in a piecemeal fashion using either hybrid EMR/EMA technique or spiral snare EMR (SS-EMR, Olympus, Keymed, UK) at our tertiary referral centre. Patient/polyp/technique-related details and short/long term endoscopic surveillance data were retrieved and analysed (chi-square/Fischer's). The aim of this study was to compare the safety, technical success and recurrence between each group (group A – hybrid EMR/EMA, group B – SS-EMR). Results: This study enrolled 56 patients in group A and 48 patients in group B. Median polyp size was 3 cm (range 2–8 cm) for group A and 5 cm (2–15 cm) for group B. The majority (64.28%) of polyps in group A had previous failed polypectomy attempts compared to only 27% of polyps in group B. There was no difference in time taken to complete the procedure between the groups (mean time for group A – 36 min vs group B – 39 min). Procedural bleeding (A vs B were 7.1% vs 18.8% p = 0.13) and delayed bleeding (A vs B were 19.6% vs 37.5%, p = 0.05) were more common in group B. There were no peforations in either group. Two (4.2%) patients in SS-EMR group developed post polypectomy syndrome and needed brief hospital admission. Four (7.1%) patients in hybrid EMR/EMA cohort developed delayed bleeding requiring admission for transfusion; all made an uneventful recovery. There was no significant difference in polyp recurrence at 24 months between the groups (A vs B 12.5% vs 8.3%, p = 0.44). No patients have required surgery to date. Conclusion: Spiral snare resection and hybrid mucosal resection/ablation modalities are both safe and feasible to eradicate recurrent fibrotic colorectal polyps. Delayed bleeding overall is significantly lower when using the hybrid resection/ablation technique though may be more severe when it does occur. Medium term outcomes appear similar in both groups with acceptable levels of endoscopically manageable recurrence. Disclosure of interest: None Declared.